Presence of Coliforms and Reduced Water Quality in the Second Biggest Reservoir in São Paulo, Brazil - Andrezza Nascimento; Lorena A. Fernandes; Carlos A. O. de Biagi; Marta A. Marcondes; Sabri Saeed Sanabani (Life)
(1) Background: The Guarapiranga reservoir, located in the metropolitan region of São Paulo (RMSP), plays an important role in supplying water to the population. However, the growing urbanization in the region, which has occurred in a disorderly manner and lacks basic sanitation infrastructure, has had a detrimental impact on the reservoir’s conditions. The aim of this study was to evaluate the physicochemical parameters and detect coliforms to determine the water quality of the Guarapiranga reservoir, as well as to characterize the microbial diversity and antimicrobial-resistance genes (ARGs) present in the reservoir water. (2) Methods: Four sampling campaigns of the Guarapiranga reservoir were carried out between October 2020 and July 2022. Physicochemical analyses, and selective microbiological culture for coliforms, as well as the extraction of bacterial DNA for subsequent sequencing and search for ARGs were carried out. (3) Results: Analysis of the physicochemical results showed a progressive reduction in the quality of the reservoir’s water, and the microbiological tests consistently showed the presence of Escherichia coli, Salmonella spp., Shigella spp. and Klebisiella spp. in the water samples collected from the reservoir. Analyses of the sequencing data showed the predominant presence of the phyla Proteobacteria, Cyanobacteria, Bacteroidetes, Verrucomicrobia, Planctomycetes, and 12 ARGs were detected in the reservoir. (4) Conclusions: The increase in sewage discharge, mainly due to the growth of irregular housing, has affected the quality of the water, as indicated by the physicochemical analysis and detection of coliforms and ARGs.